PENGARUH PENGAWASAN, FASILITAS KERJA DAN KOMPETENSI KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT. FEDERAL INTERNATIONAL FINANCE (FIF GROUP) UNIT SETIA BUDI - Butar Butar, Putri Damayanti; Sinaga, Ria Veronica; Sitanggang, Darna; Sembiring, Sabeth (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This study aims to determine the effect of supervision, work facilities and employee competence on employee performance at PT. Federal International Finance (FIF Group) Unit Setia Budi Medan. The population and sample in this study were all employees totaling 30 employees. The sampling technique used was the saturated sampling technique or census, namely the entire population will be used as a sample/respondent. From the results of the discussion, the multiple linear regression equation obtained from the results of data processing is KK = 1.901 + 0.175 P + 0.229 FK + 0.353 KO + ei, meaning that supervision, work facilities and competence have a positive and significant effect on employee performance at PT. Federal International Finance (FIF Group) Unit Setia Budi Medan. The t-test value for supervision is 2.109> t table 2.055 and the significance level is 0.045> 0.05. The work facility variable has a t-test value of 2.110> t-table 2.055 and a significance level of 0.045> 0.05. And the employee competency variable has a t-test value of 4.190> t-table 2.055 and a significance level of 0.000> 0.05. This means that supervision, work facilities and employee competency have a positive and significant partial effect on employee performance. The simultaneous effect of the F-test value is 21.813> F-table 2.97 with a significance level of 0.000 <0.05, meaning that supervision, work facilities and employee competency have a positive and significant effect on employee performance at PT. Federal International Finance (FIF Group) Unit Setia Budi Medan. The coefficient of determination (R square) value of 0.716 means that employee performance can be explained by the variables of supervision, work facilities and employee competency by 71.6%, while 28.4% can be explained by other factors not included in this study.